PROJECT RESULT ADMINISTRATION PROCEDURES IN THE STRENGTHENING COLUMN DIVISION OF PT HANDAL KARYA ABADI - Siti Zahra Giffanisa,; Dian Berliansyah Putra,; Heri Aryadi, (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
This study aims to determine the administrative procedures, obstacles, and solutions for projects in the reinforcement colo division of PT Handal Karya Abadi. The method used in this study is descriptive qualitative using interview data, observation, and documentation studies. Data were taken from the period of August 2023 to December 2023. Based on the results of the study, it can be concluded that the administrative procedures for projects in the reinforcement colo division of PT Handal Karya Abadi have been running according to Standard Operating Procedures. Administrative needs are very important considering there are quite a lot of processes related to work in the field. The Handover Minutes can be obtained when the field work has been completed to report ready for installation and the purchase order has been received from the Client. The completeness of this document is one of the administrative requirements that must be met to reach the final term, so that the payment is 100% paid off and can be forwarded to the finance & accounting department to continue the process.